Cementum regeneration strategies: Insights from development and periodontal microenvironment - Wang, Huiyi; Yang, Liu; Huang, Xin; Ma, Li; Wang, Chuan; Wang, Xiaoxuan; Cao, Zhengguo (Frontiers in Cell and Developmental Biology, 2025)
Cementum, a mineralized tissue covering the root surface of the tooth, maintains tooth stability through providing support for the attachment of periodontal ligament fibres, and protects the pulp from external damage via acting as a barrier against microbial invasion and destruction. Notably, both physiological and pathological factors may lead to the destruction of this vulnerable tissue, thus impeding its function. However, the intricate periodontal microenvironment, which consists of host cells, microbial communities, and metabolites, presents challenges to cementum regeneration. In addition, there remains a debate regarding whether the cellular origin of cementum is derived from mesenchymal cells or epithelial cells. Due to the limitations of traditional regenerative surgeries in achieving complete cementum regeneration, researchers are exploring new strategies based on cementum development and the periodontal microenvironment. Our group has revealed the crucial regulatory mechanisms in cementoblast differentiation and developed engineering materials for cementum regeneration. Drawing upon the latest research on cementum development and regeneration, alongside the comprehensive studies undertaken by our research group over the years, this review systematically consolidates current knowledge on cementum development and the regulatory functions of the periodontal microenvironment. It emphasizes mechanisms such as metabolic reprogramming, epigenetic modifications, and immune-stem cell interactions. Furthermore, the review seeks to provide innovative, target-oriented insights for strategies aimed at cementum regeneration, grounded in the understanding of cementum development and the periodontal microenvironment.